Enriching Rotifers with “Premium” Microalgae. Nannochloropsis gaditana - Ferreira, Martiña (2016)
The nutritive quality of Nannochloropsis gaditana cultured semicontinuously with different daily renewal rates was tested as a diet for short-term enrichment of the rotifer Brachionus plicatilis. After 24 h, dramatic differences in the survival, dry weight, and biochemical composition of the rotifers depending on the renewal rate of microalgal cultures were observed. Survival after the feeding period increased with increasing renewal rates. Rotifers fed microalgae from low renewal rate, nutrient-deficient cultures showed low dry weight and organic contents very similar to those of the initial rotifers that were starved for 12 h before the start of the feeding period. On the contrary, rotifers fed nutrientsufficient microalgal cells underwent up to twofold increases of dry weight and protein, lipid, and carbohydrate contents with regard to rotifers fed nutrient-depleted N. gaditana. Consequently, feed conversion rate decreased in these conditions, indicating a better assimilation of the microalgal biomass obtained at high renewal rates. No single microalgal biochemical parameter among those studied can explain the response of the filter feeder. Similarly to gross composition, EPA and n-3 contents in rotifers fed microalgae from nutrient-sufficient cultures were double than the contents found in rotifers fed nutrient-limited microalgae. In addition, very high positive correlations between the contents of EPA and n-3 in N. gaditana and B. plicatilis were observed. These results demonstrate that selecting the appropriate conditions of semicontinuous culture can strongly enhance the nutritional value of microalgae that is reflected in the growth and biochemical composition of the filter-feeder even in short exposure periods.